Morbidity in neurofibromatosis 1: Epidemiological perspectives on breast cancer and diabetes - Kallionpää, Roope (fi=Turun yliopisto|en=University of Turku|, 2022)
Neurofibromatosis type 1 (NF1) is a dominantly inherited rare disorder caused by pathogenic variants of the NF1 tumor suppressor gene. The syndrome can be diagnosed based on its clinical manifestations, such as café-au-lait macules, skinfold freckling, and benign cutaneous neurofibroma tumors. NF1 affects several organ systems, yet it is best known as a tumor predisposition syndrome. In this thesis, a Finnish cohort of 1,476 individuals with NF1 was used to study the prevalence of NF1 and the risks for breast cancer and diabetes among individuals with NF1. For a more precise assessment of the risk for contralateral breast cancer in NF1, the Finnish NF1 cohort was analyzed together with four other European NF1 cohorts. Moreover, the effect of NF1 on the concentration of circulating free plasma DNA (cfDNA) was assessed in a small-scale clinical study. Breast cancer diagnoses of individuals with NF1 were obtained from the Finnish Cancer Registry. Diagnoses of diabetes were inferred from drug purchases and hospital visits and hospital stays. The characteristics of NF1-related breast cancer were also analyzed. The results demonstrate that the overall prevalence of NF1 may be as high as 1/2,052. NF1 is associated with increased mortality throughout the lifetime, and the age-specific prevalence of NF1 declines in older age groups. Women with NF1 face a marked risk for breast cancer, and the risk for being diagnosed with breast cancer is 7.8% by 50 years of age. The survival after NF1-related breast cancer is worse compared to breast cancer in the general population. Breast cancers diagnosed in individuals with NF1 also exhibit poor prognostic factors, such as hormone receptor negativity. Moreover, women with NF1 and breast cancer have a 16% risk for contralateral breast cancer within 20 years. In contrast, the risk for diabetes and type 2 diabetes, in particular, is decreased among individuals with NF1. The NF1 syndrome, as such, may not significantly alter plasma cfDNA concentration. The results highlight the need for identifying all individuals with NF1 in order to provide them surveillance for NF1-related complications, such as breast cancer. The findings demonstrate the role of the NF1 gene in the pathogenesis of two common diseases, namely breast cancer and diabetes.

Sairastavuus tyypin 1 neurofibromatoosissa: epidemiologisia näkökulmia rintasyöpään ja diabetekseen Tyypin 1 neurofibromatoosi (NF1) on vallitsevasti periytyvä harvinaissairaus, joka aiheutuu muutoksista NF1-kasvunrajoitegeenissä. Sairaus voidaan diagnosoida kliinisten oireiden, kuten ihon maitokahviläiskien, taivealueiden kesakoiden ja hyvänlaatuisten neurofibrooma-ihokasvainten perusteella. NF1 vaikuttaa moniin elinjärjestelmiin, mutta parhaiten se tunnetaan kasvainalttiusoireyhtymänä. Tässä tutkimuksessa tarkasteltiin NF1:n yleisyyttä sekä potilaiden alttiutta sairastua rintasyöpään ja diabetekseen. Tutkimuksessa käytettiin 1476 henkilön suomalaista NF1-kohorttia. Vastakkaisen rinnan rintasyövän riskiä tutkittaessa hyödynnettiin tietoja myös neljästä muusta eurooppalaisesta NF1-kohortista. Lisäksi tarkasteltiin NF1:n vaikutusta plasman vapaiden nukleiinihappojen pitoisuuteen. NF1-potilaiden rintasyöpädiagnoosit haettiin Suomen Syöpärekisteristä. Diabetesdiagnoosit pääteltiin lääkeostotiedoista sekä sairaalakäynneistä ja -jaksoista. Lisäksi tarkasteltiin NF1:een liittyvän rintasyövän ominaisuuksia. Tulokset osoittavat, että NF1:n vallitsevuus on jopa 1/2052. NF1 aiheuttaa lisääntynyttä kuolleisuutta kaikissa ikäryhmissä, minkä vuoksi NF1:n vallitsevuus laskee vanhemmissa ikäryhmissä. NF1:een liittyy merkittävä rintasyöpäriski, ja NF1:tä sairastavilla naisilla on 7,8 %:n todennäköisyys sairastua rintasyöpään ennen 50 vuoden ikää. NF1 huonontaa rintasyövän ennustetta, ja NF1-naisten rintasyövät ovat usein hormonireseptorinegatiivisia. Lisäksi rintasyöpään sairastuneilla NF1- naisilla on 16 %:n riski sairastua vastakkaisen rinnan rintasyöpään 20 vuoden kuluessa. Sen sijaan erityisesti tyypin 2 diabeteksen riski on NF1:ssä pienempi kuin vertailuväestössä. NF1-sairaus itsessään ei vaikuta merkittävästi muuttavan plasman vapaiden nukleiinihappojen pitoisuutta. Tulokset korostavat tarvetta tunnistaa kaikki NF1:tä sairastavat henkilöt, jotta he pääsevät taudin edellyttämän seurannan piiriin. Tulosten perusteella NF1-geeni vaikuttaa kahden yleisen sairauden, rintasyövän ja diabeteksen, kehitykseen